2019
DOI: 10.29252/shefa.7.2.23
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelationship between Job Stress with the Immune System and Functional Memory of Women Working in Diagnostic Laboratories

Abstract: Job s tress is a psychological s tate that results from a feeling of inconsis tency between capacities and situations and a kind of non-specific response to all factors that can affect the immune sys tem and functional memory. This s tudy was aimed to inves tigate the relationship between job s tress with the immune sys tem and functional memory of women working in diagnos tic laboratories. Materials and Methods: Correlation method was used to evaluate the hypotheses. The s tudy population includes all women e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…As well, 35.1% of the cases in the HCSG had obtained an IES-R score of 37 or above, indicating that the COVID-19 event impact was at the level of immunosuppression.The study results also revealed that the PTSD severity (based on the IES-R sub-scales) was higher in the HCSG and OCSG than in the GPG.Of note, different types of stress can have negative effects on the immune system. In other words, stress weakens the human immune system(Sadeghi Yarandi et al, 2018). In the present study, the IES-R mean score and the PTSD severity (viz.…”
mentioning
confidence: 46%
See 1 more Smart Citation
“…As well, 35.1% of the cases in the HCSG had obtained an IES-R score of 37 or above, indicating that the COVID-19 event impact was at the level of immunosuppression.The study results also revealed that the PTSD severity (based on the IES-R sub-scales) was higher in the HCSG and OCSG than in the GPG.Of note, different types of stress can have negative effects on the immune system. In other words, stress weakens the human immune system(Sadeghi Yarandi et al, 2018). In the present study, the IES-R mean score and the PTSD severity (viz.…”
mentioning
confidence: 46%
“…Of note, different types of stress can have negative effects on the immune system. In other words, stress weakens the human immune system (Sadeghi Yarandi et al, 2018 ). In the present study, the IES‐R mean score and the PTSD severity (viz.…”
Section: Discussionmentioning
confidence: 99%
“…Because coronavirus has spread rapidly around the world, it caused fear andanxiety among the general population, especially among certain groups such as pregnant women (3). Nowadays, the effects of stress on the immune system are well known, as a result, humans are prone to all kinds of mental and physical illnesses (4). One of the determinants of mental health is the quality of life (QoL).…”
Section: Introductionmentioning
confidence: 99%
“…Because coronavirus has spread rapidly around the world, it caused fear, anxiety among the general population, especially among certain groups such as pregnant women (3). Nowadays, the effects of stress on the immune system are well known, as a result, humans are prone to all kinds of mental and physical illnesses (4). One of the determinants of mental health is the quality of life (QoL).…”
Section: Introductionmentioning
confidence: 99%